THE INFLUENCE OF PRINCIPAL SUPERVISION, MASTERY OF TECHNOLOGY, AND TEACHER WORK MOTIVATION ON THE PERFORMANCE OF HINDU RELIGIOUS EDUCATION - Gusti Ayu Suasthi; I Ketut Winantra; Ida Ayu Gede Yadnyawati (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2025)
Changes in teaching systems and methods are the root of the problem in the performance. There is still no significant improvement in teacher performance, so there is a need for a study of the performance of Hindu religious education and moral education teachers in Tabanan Regency. Methods: This research is a type of quantitative research by distributing questionnaires in the form of questionnaires and google form, which was given to Hindu religious education and moral education teachers at junior high schools in Tabanan Regency. Finding: From the research results, data analysis was carried out using the SPSS program in processing, questionnaire trial data and descriptive analysis of each variable item, and using SEM PLS analysis, to find the direct and indirect influence of the three independent variables on teacher performance. Conclusion: 1) The principal's supervision influences performance. (2) Mastery of technology has a positive effect on teacher performance. (3) Teacher work motivation has a positive and significant effect on teacher performance. (4) Mastery of technology has an indirect influence on teacher performance. So it can be concluded that the three variables can also be explained as having simultaneous influence.